Perioperative systemic chemotherapy for appendiceal mucinous carcinoma peritonei treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 7 (28th December 2013) - Blackham, Aaron U.; Swett, Katrina; Eng, Cathy; Sirintrapun, Joseph; Bergman, Simon; Geisinger, Kim R; Votanopoulos, Konstantinos; Stewart, John H.; Shen, Perry; Levine, Edward A.
<x xml:space="preserve">Abstract</x> Background The role of systemic chemotherapy (SC) in conjunction with cytoreductive surgery (CS) with hyperthermic intraperitoneal chemotherapy (HIPEC) in appendiceal mucinous carcinoma peritonei (MCP) is unknown. Methods A retrospective review (1999–2011) of MCP patients who had undergone CS/HIPEC with or without perioperative SC. Results Twenty‐two low‐grade MCP patients treated with CS/HIPEC and SC were matched to patients who received CS/HIPEC alone. Median overall survival (OS) was 107 months for patients treated with perioperative SC compared to 72 without (P = 0.46). CS/HIPEC was performed on 109 patients with high‐grade MCP: 70 were treated with perioperative SC, while 39 were not. Median OS (22.1 vs. 19.6 months, P = 0.74) and progression‐free survival (PFS) (10.9 vs. 7.0 months, P = 0.47) were similar in patients treated with SC compared to CS/HIPEC alone. Progression while on pre‐operative SC was seen in eight patients (17%), while four (8%) had a partial response. Treatment with post‐operative SC was associated with longer PFS (13.6 months) compared to pre‐operative SC (6.8 months, P < 0.01) and CS/HIPEC alone (7.0 months, P = 0.03). Conclusions Post‐operative SC appears to improve PFS in patients with high‐grade appendiceal MCP treated with CS/HIPEC. In contrast, there is no evidence to support the routine use of perioperative SC in low‐grade disease. J. Surg. Oncol 2014; 109:740–745. © 2013 Wiley Periodicals, Inc.